Impact of Door-To-Balloon Time on Long-Term Mortality after Primary PCI - Khan, Muhammad Niaz; Ali Shah , Hamid; Ali , Nasir; Rashid Qureshi, Amir; Ullah , Abid; Muhammad Salman, (Indus Journal of Bioscience Research, 2024)
Objective:  To evaluate the impact of door-to-balloon (D2B) time on long-term mortality and adverse outcomes in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar.Methodology:  A prospective observational study was conducted from January 2022 to December 2022, including 320 STEMI patients. Patients were categorized into two groups based on D2B times: